Archaeology [videorecording] - Foiles, Stacey; Grant, Eleanor; Naughton, Tom; Valcour, Nicholas (Discovery Communications, 1994)
Discovers the raw archaeological materials that gives insights as to who were the Philistines and the historical counterpart to the scriptural people who harassed the Israelites for many generations. Scientists find proofs of the killer quakes in the bible in the ruins of ancient sites.